The Comparison of Transportation Network Node Density in Balikpapan City in 2019 and 2025 - Iwan Aminto Ardi; Hidayati, Solikhah Retno; Kamal, Passatama Apryanda (ReTII, 2025)
This research analyzes the concentration of land transport network intersections in Balikpapan City for 2019 and projects the figures for 2025. Balikpapan, as the primary entry and logistics hub for Indonesia’s planned new capital, is undergoing significant infrastructure changes, necessitating this study to assess road network density variations pre- and post-major development projects. The methodology used is Kernel Density spatial analysis, applying data from the 2019 Indonesian Topographic Map and 2025 Online Street Map, with results visualized through graduated color schemes. Key findings show a substantial increase in network intensity and geographical coverage between the two periods. In 2019, the peak density (81.71) was primarily concentrated in the southern and central parts of the city. By 2025, the peak density value is projected to rise to 111.71, with high-density zones visibly expanding to cover nearly all northern and eastern areas. This shift suggests considerable infrastructure growth and a more balanced distribution across the administrative area, leading to a change in transportation focal points. The study recommends future strategies focusing on upgrading mass transit, reducing reliance on personal vehicles, and implementing comprehensive traffic control measures to improve the efficiency of the burgeoning network.